2008
DOI: 10.1021/jp805259q
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Polyhedral Oligomeric Silsesquioxane Modified Clay and Its Application in Polymerization of Macrocyclic Polyester Oligomers

Abstract: Novel porous aminopropyllsooctyl polyhedral oligomeric silsesquioxane (POSS) modified montmorillonite clay complexes (POSS-Mts) with large interlayer distance and specific surface area have been successfully prepared via ion-exchange reaction and followed by freeze-drying treatment. The morphology of the POSS-Mts is highly influenced by the POSS concentration, pH of the suspension and drying procedure, but the interlayer distance of the POSS-Mts does not change much when the POSS concentration is above 0.4 CEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 22 publications
0
50
0
1
Order By: Relevance
“…[134][135][136][137][138] An increasing amount of reports on pCBT/organoclay nanocomposites can also be found. 14,65,[139][140][141][142][143][144][145][146] The low viscosity of molten or dissolved oligomers is utilized to obtain a CBT-intercalated organoclay. Subsequent ROP causes then an increase in interlayer distance along with the disintegration of the layered clay structure, as shown in figure 22.…”
Section: Physical Blendingmentioning
confidence: 99%
See 1 more Smart Citation
“…[134][135][136][137][138] An increasing amount of reports on pCBT/organoclay nanocomposites can also be found. 14,65,[139][140][141][142][143][144][145][146] The low viscosity of molten or dissolved oligomers is utilized to obtain a CBT-intercalated organoclay. Subsequent ROP causes then an increase in interlayer distance along with the disintegration of the layered clay structure, as shown in figure 22.…”
Section: Physical Blendingmentioning
confidence: 99%
“…Only few reports on complete clay exfoliation of the final nanocomposites are available, 139,146 whereas intercalated or flocculated-intercalated structures are more commonly observed. [141][142][143][144][145] Although the organoclay is successfully intercalated with CBT oligomers or even completely exfoliated before ROP, the silicate layers tend to reorganize due to the low viscosity of the molten CBT during ROP. Thus the exfoliated structure is lost and a flocculated-intercalated structure is obtained after polymerization.…”
Section: Physical Blendingmentioning
confidence: 99%
“…Although several researchers have shown that the organoclay was successfully intercalated with CBT oligomers or even completely exfoliated prior to ROP, the silicate layers tended to reorganize due to the low viscosity of the molten CBT during ROP. Consequently, the exfoliated structure was lost and a flocculated-intercalated structure was obtained after polymerization [16,19,20]. Similarly, clay nanocomposites made from other types of cyclic oligomers have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, pCBT is inherently brittle which has been ascribed to the formation of large perfect crystals with a lack of intercrystalline tie molecules [8], different crystalline morphologies [10] as well as to a low molecular weight [11,12]. An increasing amount of publications dealing with pCBT/organoclay nanocomposites can be found in the literature [7,[13][14][15][16][17][18][19][20][21]; however, despite this considerable body of papers, little is known about the mechanical properties of these materials [15,18,20] and information about the deformation behaviour is rare. Most researchers employ the low viscosity of molten or dissolved oligomers in order to obtain a CBT-intercalated organoclay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation